Evaluation of the Effect of Dual-Stage Aging and RRA on the Hardening and Corrosion Resistance of AW7075 Alloy - Aleksandra Ładak; Mateusz Cichoń; Marzena Lachowicz (Corrosion and Materials Degradation, 2022)
The corrosion resistance of the AW7075 alloy after RRA treatment was evaluated. The corrosion rate in the NSS test was assessed and the electrochemical parameters were determined. The results were compared with the results obtained for the alloy subjected to conventional aging (T6) and dual-stage aging (DA). In order to determine the state of alloy hardening, the tests were carried out simultaneously with the material hardness measurements and microscopic examinations. The hardness of the AW7075 alloy increased in the following order: DA < T6 < RRA. The tests revealed that the achieved increase in strengthening was correlated with the preservation of high resistance to general corrosion of the alloy after RRA treatment. After the corrosion tests, SEM microscopic observations were also carried out to determine the corrosion features. The corrosion rate can be arranged in the following order: RRA < T6 ≈ DA. At the same time, the alloy after RRA was characterized by the lowest value of the corrosion potential and the open circuit. The corrosion potential value can be presented in increasing order: RRA < T6 ≈ DA. The corrosion behavior of the aluminum alloy after dual-stage aging was similar to that of T6. However, it was accompanied by a decline in hardening.